Acquired cytomegaly-Description of three cases - Patrycja Kałużna; Ewa Maria Łuczkowska; Ksenia Mazur; Beata Łoniewska (Elsevier, 2024)
The case reports describe the hospitalization of three extremely premature infants who developed cytomegalovirus (CMV) infection. The most probable source of infection was their mothers' milk. Although the infants were already stable and had survived for several weeks, their health and lives were threatened by the CMV infection. Despite the Polish recommendations for feeding extreme preterm infants with fresh breast milk, we have implemented our own management procedure due to the specific clinical circumstances. We test the breast milk of a seropositive mother for CMV early on and then provide the infant with pasteurized milk from 8 days of age until the test results are available or up to 34 postmenstrual age if CMV presence is confirmed. This procedure ensures the health and safety of the infants while providing them with necessary nutrients. We also outline the treatment of premature infants, potential complications during therapy, and monitoring treatment effects. We describe milk pasteurization techniques and the differences in composition due to the processes used. The paper provides also a summary of practices for feeding extremely premature infants with milk from seropositive mothers in other countries.